2010
DOI: 10.21273/hortsci.45.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from Six Herbal Plants for Biocontrol of the Maize Weevil

Abstract: Essential oils from sweet basil (Ocimum basilicum L.), holy basil (O. americanum L.), hairy basil (O. tenuiflorum L.), lime (Citrus aurantifolia Swingle), kaffir lime (C. hystrix DC.), and clove (Eugenia caryophyllus L.) were isolated by simultaneous distillation extraction. Toxicity assays against the maize weevil (Sitophilus zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Mwangangi and Mutisya (2013) used O. basilicum extract against maize weevil and confirmed that O. basilicum extract has potential to control this pest effectively. Kerdchoechuen et al (2010) reported that sweet O. basilicum oil extract can caused 96 to 100% mortality of maize weevil, 5 days after application. It is concluded from current study, plant extracts have a potential to control maize weevil without causing lethal effects on stored commodity and environment and safer for health.…”
Section: Resultsmentioning
confidence: 99%
“…Mwangangi and Mutisya (2013) used O. basilicum extract against maize weevil and confirmed that O. basilicum extract has potential to control this pest effectively. Kerdchoechuen et al (2010) reported that sweet O. basilicum oil extract can caused 96 to 100% mortality of maize weevil, 5 days after application. It is concluded from current study, plant extracts have a potential to control maize weevil without causing lethal effects on stored commodity and environment and safer for health.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, medium polarity solvents (diethyl ether, dichloromethane or ethyl acetate) extract more polar and higher MW compounds such as hexadecanal (Naef and Velluz, 2001; Gancel et al, 2002; Chisholm et al, 2003a,b; Cannon et al, 2015), squalene (Cheong et al, 2011b; Jiang et al, 2011), linoleic acid (Cheong et al, 2011b, 2012; Jiang et al, 2011), heptadecanoic acid (Delort and Jaquier, 2009; Jiang et al, 2011) or neophytadiene (Delort and Jaquier, 2009; Delort et al, 2015) than distillation or cold press extraction, and it fails to extract many monoterpene and sesquiterpene compounds which are characteristic of Citrus EOs (Jiang et al, 2011). Moreover, there are other minority extraction methods that use also organic solvents such as simultaneous distillation and extraction (SDE) (Akakabe et al, 2008; Kerdchoechuen et al, 2010; Sun et al, 2014a), microwave-assisted extraction (MAE) (Sun et al, 2014a; Liu et al, 2015), and ultrasonic-assisted extraction (UAE) (Alissandrakis et al, 2003; Darjazi, 2011b; Liu et al, 2012; Sun et al, 2014a; Zhang et al, 2017).…”
Section: Techniques To Extract Citrus Volatile Compoundsmentioning
confidence: 99%
“…Some authors have reported the toxicity of O. basilicum essential oil on C. maculatus (KEITA et al, 2000;PASCUAL-VILLALOBOS et al, 2003;ALVES et al, 2015) and S. zeamais (MATTA et al, 2010). However, no study has analyzed the toxicity of the essential oils of the hybrids tested in this work against C. maculatus and S. zeamais.…”
Section: Discussionmentioning
confidence: 87%
“…The toxicity of basil essential oil has already been confirmed against Acanthoscelides obtectus (MAZZONETTO; VENDRAMIM, 2003), Callosobruchus maculatus (PASCUAL-VILLALOBOS et al, 2003), Rhyzopertha dominica (LÓPEZ et al, 2008), Sitophilus zeamais (ASAWALAM et al, 2008;MATTA et al, 2010), Tribolium castaneum (MISHRA et al, 2012), Zabrotes subfasciatus (FRANÇA et al, 2012), and Sitophilus oryzae (POPOVIĆ et al, 2006). However, no research has been carried out against C. maculatus and S. zeamais and the essential oil of basil hybrids using cultivars Sweet Dani, Maria Bonita, Genovese, and Cinnamom.…”
Section: Introductionmentioning
confidence: 95%